Network Management System (NMS)Berbasis Zabbix Pada Server Universitas Bina Darma - Suryayusra; Wildan Maula (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The rapid growth of information technology in the education sector requires a reliable and stable network infrastructure to support academic and operational activities. Universitas Bina Darma, as an institution that widely implements digital services, needs an effective monitoring system capable of ensuring service availability and detecting disruptions in real time. This research aims to implement a Zabbix-based Network Management System (NMS) as a solution for monitoring the university's IT infrastructure, including servers and network devices. The study employs a descriptive method with an experimental approach, involving the installation, configuration, implementation, and performance testing of the Zabbix system within the university’s server environment. The results show that Zabbix is able to provide automatic notifications during anomalies, deliver accurate performance metrics, and improve the efficiency of troubleshooting processes. This implementation enhances the overall effectiveness of network management and supports future IT infrastructure planning at Universitas Bina Darma.